Depression in young autistic people: A scoping review. (October 2021) - Kim, Soo Youn; Lecavalier, Luc
Highlights: Four major themes emerged: Prevalence and clinical presentation, Associated features, Intervention, Psychometric properties of instruments. The estimated prevalence varied significantly between and 8 and 26%. Anhedonia appeared to be the dominant feature compared to typically developing children and adolescents. Factors related to social impairment were the most studied psychological correlates. Very few studies evaluated intervention specifically targeting depression and instruments of depressive symptoms in autism spectrum disorder. Abstract: Background: Depressive symptoms are prevalent in autistic individuals. However, there is a limited understanding of what is known about depression in autistic children and adolescents. The aim of this scoping review is to examine the themes and the quality of studies on depressive symptoms in young autistic people. Method: A search was conducted on the electronic databases PubMed and PsycINFO examining the themes and quality of the studies. Participant demographics and instruments used were also reviewed. Results: Fifty-five studies met inclusion criteria. Four major themes emerged across the reviewed studies: 1) Prevalence and clinical presentation, 2) Associated features, 3) Intervention, 4) Psychometric properties. Thirty-one of the 55 studies (56%) were rated as Strong, 11 studies (20%) rated as Adequate, and 13 studies (24%) as Weak . Most studies were conducted on adolescents with IQ > 70. A variety of instruments were used to assess depressive symptoms. Conclusions: Most studies have been conducted in the past decade. Clinical presentation and the associated features were the most studied themes. Very little is known on intervention targeting depression or studies examining psychometric properties of instruments in young autistic people. Further studies are needed to address the gap in research in the following area: 1) Validation of instruments used, 2) Symptoms in those with intellectual disability, 3) Longitudinal studies exploring the course of depression over time, 4) Correlates of depressive symptoms, and 5) Intervention specifically targeting depressive symptoms in ASD.